A new stem nematode, Ditylenchus oncogenus n. sp. (Nematoda: Tylenchida), parasitizing sowthistle from Adriatic coast dunes in southern Italy. Issue 2 (3rd February 2015) - Vovlas, N.; Troccoli, A.; Palomares-Rius, J.E.; De Luca, F.; Cantalapiedra-Navarrete, C.; Liébanas, G.; Landa, B.B.; Subbotin, S.A.; Castillo, P.
Abstract: Morphological and molecular analyses of a stem nematode causing a severe disease on infected sowthistle ( Sonchus bulbosus ) plants, involving the formation of gall-like structures on infected leaves and stems, have led to the description of a new species named Ditylenchus oncogenus n. sp. Morphologically, the new species is characterized by a medium to large body size (all adults more than 1 mm in length); a delicate stylet (9.0–11.0 μm long) with minute, rounded knobs; a long post-vulval uterine sac ( c . 65% of the vulva–anus distance); six incisures at the lateral fields and characteristic D. destructor -pattern of spicules (with pronounced ventral tumulus and anteriorly pointed, less sclerotized, cuticle parts present within the lamina). The results of molecular analysis of rRNA gene sequences, including the D2–D3 expansion regions of 28S rRNA, internal transcribed spacer (ITS) rRNA, partial 18S rRNA gene, the protein-coding mitochondrial gene, cytochrome oxidase c subunit I ( COI ), and the heat-shock protein 90 ( hsp90 ) gene, support the new species status. The results of a host-suitability test indicated that the new species does not parasitize potato ( Solanum tuberosum ) tubers and broad bean ( Vicia faba ) seedlings. Histopathological observations on naturally infected sowthistle tissues revealed that D. oncogenus n. sp. causes floral stem neoplasia and midrib leaf gall formation on the type, and to date only known, host. The galls were characterized by extensive hyperplasia, where several necrotic cells in the neoplasic area were directly damaged by feeding of the nematode, whereas a number of adjacent cells showed typical cytological changes, such as granulated cytoplasm with hypertrophied nuclei and nucleoli.